Changes in the Respiratory, Enzymatic, and Swelling and Contraction Properties of Mitochondria from Colytedons of Phaseolus vulgaris L. during Germination - Malhotra, Surjit S. (1970)
Mitochondria isolated from cotyledons of germinating wax beans (Phaseolus vulgaris L.) showed fairly good respiratory control on days 1 and 2 after planting. The respiratory control was completely lost from days 3 to 5. During this period mitochondria were shown to be very leaky, losing about 88% of their total nicotinamide adenine dinucleotide to the suspending medium in a short time. The respiratory control was partially recovered by day 7, after which it completely disappeared again. By the use of differential centrifugation, the mitochondria were divided into subfractions by sequential centrifugation: 10,000g for 5 minutes, 25,000g for 5 minutes, and 40,000g for 5 minutes. The 10,000g subfraction was responsible for the recovery of mitochondrial activity (respiratory control value, adenosine diphosphate to oxygen ratio, and rate of oxygen utilization), on day 7. Activities of succinate dehydrogenase, cytochrome oxidase, pyruvate dehydrogenase, and isocitrate dehydrogenase from different mitochondrial subfractions of aging cotyledons were determined. In general, the enzyme activities, adenosine diphosphate to oxygen ratios, and the ability of mitochondria to swell and contract followed the same pattern as for respiratory control.